1993
DOI: 10.7883/yoken1952.46.75
|View full text |Cite
|
Sign up to set email alerts
|

Epizootiological Study of Hantavirus Infection Among Rattus Norvegicus in Tokyo Bay Area, Japan

Abstract: SUMMARY: The prevalence of antibodies against hantavirus in 413 rats (Rattus norvegicus) captured in eight regions of the Tokyo Bay area from 1983 to 1992 were examined by the indicrect fluorescent antibody test. Antibody-positive rats were found in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
2
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
5
2
1
Order By: Relevance
“…In R. norvegicus, transmission of the virus occurred more frequently in adult rats than in juvenile ones. The same mode of transmission of the virus in rats has been reported in other countries (6,7). R. norvegicus is thought to be the most important reservoir of Seoul virus in Indonesia as well as in other countries.…”
Section: Seoul Virus Is a Member Of Genussupporting
confidence: 73%
“…In R. norvegicus, transmission of the virus occurred more frequently in adult rats than in juvenile ones. The same mode of transmission of the virus in rats has been reported in other countries (6,7). R. norvegicus is thought to be the most important reservoir of Seoul virus in Indonesia as well as in other countries.…”
Section: Seoul Virus Is a Member Of Genussupporting
confidence: 73%
“…and 1990 (8) and in Haneda Airport in 1983, no antibody-positive case was shown in the present study. Though the sera which showed specific granular staining in the infected cell cytoplasm in dilutions higher than 1:32 are regarded as IFA positive, in sera of low IFA titers, it seems to be quite difficult to exclude completely false positive cases.…”
contrasting
confidence: 58%
“…We reported that antibody-positive rats were found in Tokyo Port, from 1983 to 1986, while no positive case from 1987 to 1990 (8). In the present study,…”
supporting
confidence: 44%
See 1 more Smart Citation
“…Similar findings were also observed in Japan (Morita et al 1983;Sugiyama et al 1984;Arikawa et al 1986;Sugiyama et al 1993;Ma et al 1995;Lokugamage et al 2004), Korea (Lee 1989), and Indonesia (Ibrahim et al 1996). In order to determine whether seaports may play the role as a source of hantavirus, we captured rodents from different localities on relatively isolated islets along the coast of Fujian Province, mainland China, screened for antibodies against hantavirus, and compared the seroprevalences in these localities.…”
Section: Introductionsupporting
confidence: 60%